In search of the good life : a pedagogy for troubled times - Dallmayr, Fred R. (Fred Reinhard), 1928- (University Press of Kentucky, 2007)
To whom should we look for moral guidance during times of global violence, scarcity, and corruption? For two millennia, Aristotle's writings have taught that the ethically "good life" is the highest purpose of human existence. In In Search of the Good Life, renowned philosopher Fred Dallmayr traces the development of this notion, illuminating the connections between Greek philosophy, Judeo-Christian tradition, Eastern religions, and postindustrial social criticism. Dallmayr searches the writings of Bonaventure, Nicolaus of Cusa, Leibniz, Montesquieu, and others, for models of the good life